Implementasi Metode Digital Storyboarding Pada Naskah Serial Animasi 2d Sirah Nabawiyah Episode 1 - Waffa Alhusna; Sheanny Ocmi Sakti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to analyze the implementation of digital storyboarding in translating the script of Sirah Nabawiyah Episode 1 into a storyboard, focusing on the visual conformity with the script. Animation has rapidly evolved as a creative industry medium that combines audio and visual elements, playing a significant role not only as entertainment but also as an educational tool across various age groups. This study highlights the special challenges of Islamic historical animation, which requires visual appeal alongside historical accuracy and adherence to Islamic representation guidelines. The pre-production phase, especially storyboard creation, is critical in minimizing production errors and costs. Sirah Nabawiyah, a collaborative animated series between Durioo and Piapi Studio, targets children aged 6-12 years and aims to present the history of Prophet Muhammad SAW with simple visuals and narrative styles accessible to young audiences. Materials and methods involved the use of digital storyboarding techniques to transform the written script into comprehensive visual guides, determining effective shot composition and smooth narrative flow. Adobe Photoshop was utilized as the primary software tool. The process facilitated technical collaboration across teams while ensuring adherence to client guidelines established during the conceptual stage. Results demonstrated a high level of visual consistency with the script, with the storyboard effectively conveying moral and historical messages tailored for children. The use of digital storyboarding improved workflow efficiency and accuracy, producing outputs that meet technical standards and narrative requirements. Conclusions indicate that digital storyboarding is an effective method for producing Islamic educational animation, ensuring continuity between script, storyboard, and animatic stages while maintaining visual and technical quality.